Faktor Faktor Yang Memengaruhi Kepatuhan Pembayaran Pajak Bumi dan Bangunan Di Desa Gidangelo, Welahan, Kabupaten Jepara - Azzah Tualifah; Bayu Tri Cahya (P3M Politeknik Negeri Bengkalis, 2025)
This study aims to examine and analyze the various factors that influence the level of compliance in the payment of Land and Building Tax (PBB) in Gidangelo Village. This research is the first study that specifically highlights PBB payment compliance with a focus on villages that rank high in compliance in the Jepara Regency area. The independent variables in this study include tax socialization, income level, and awareness of taxpayers. The object of the research is the community of Gidangelo Village, Nalumsari Subdistrict, Jepara Regency, while the subjects are individuals who have been registered as PBB taxpayers and have a history of paying the tax. The number of samples analyzed in this study were 92 respondents. The method used is an associative quantitative approach with primary data collection through distributing questionnaires directly from house to house. The results of the analysis show that tax socialization does not have a significant effect on the level of compliance, while the variables of income level and taxpayer awareness have a significant effect on compliance with paying PBB. This research has limitations on the validity of the data, considering that there were questionnaires filled out by parties representing actual respondents.